The impact of breathing rate on the cardiac autonomic dynamics among children with cerebral palsy compared to typically developed controls. (17th February 2019) - Amichai, Taly; Eylon, Sharon; Berger, Itai; Katz-Leurer, Michal
ABSTRACT: Purpose : To describe the immediate effect of breathing rate on heart rate (HR) and heart rate variability (HRV) in children with cerebral palsy (CP) and a control group of typically developed (TD) age and gender-matched children. Methods : Twenty children with CP at gross motor function classification system levels I–III and 20 TD children aged 6–11 participated in the study. HR was monitored at rest and during paced breathing with biofeedback. Respiratory measures were assessed by KoKo spirometry. Results : Children with CP have lower spirometry and HRV values at rest compared to TD children. The mean reduction of breathing rate during paced breathing among children with CP was significantly smaller. Nonetheless, while practicing paced breathing, both groups reduced their breathing rate and increased their HRV. Conclusions : The results of the current work present the immediate effect of paced breathing on HRV parameters in CP and TD children. Further studies are needed to investigate the effect of long-term treatment focusing on paced breathing for children with CP.